2017
DOI: 10.1016/j.jmps.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the crack path by controlling the microstructure

Abstract: We explore the possibility of engineering the crack path by controlling a material's microstructure in order to increase its crack growth resistance. Attention is confined to a specific type of microstructure that is encountered in a variety of structural metals and alloys-second phase particles distributed in a ductile matrix. The type of controlled microstructure modeled is characterized by various sinusoidal distributions of particles with fixed mean particle spacing. Three dimensional, finite deformation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…As in refs. [21,[30][31][32][33], eight point Gaussian integration is used in each twenty-node element for integrating the internal force contributions and twenty-seven point Gaussian integration is used for the element mass matrix. Lumped masses are used so that the mass matrix is diagonal.…”
Section: Unit Cell Finite Element Modelmentioning
confidence: 99%
“…As in refs. [21,[30][31][32][33], eight point Gaussian integration is used in each twenty-node element for integrating the internal force contributions and twenty-seven point Gaussian integration is used for the element mass matrix. Lumped masses are used so that the mass matrix is diagonal.…”
Section: Unit Cell Finite Element Modelmentioning
confidence: 99%
“…Several physical processes can be viewed as a problem of path selection, for example, flow of a river stream [1] or crack growth in a complex heterogeneous material microstructure [2][3][4]. Although the problems of path selection for flow of a river stream and of crack growth in a heterogeneous material involve very different length-scales, their solutions share common features.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that it is possible to engineer crack paths by controlling the distribution of second phase particles in a ductile matrix to increase the material's crack growth resistance [3]. In [3], the controlled microstructure was char-acterized by various sinusoidal distributions of particles with fixed mean particle spacing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly periodic, strenuous, and sinuous crack path for metallic glass is surprising and has not been reported before (details on the geometry and statistics of saw tooth cracks can be found in Figures S5 and S6 in the Supporting Information). Simulations have shown that by tailoring the amplitude and wavelength of this type of saw tooth cracks, fracture toughness can be greatly improved . Furthermore the edge‐on view (Figure c,d) of saw‐tooth cracks reveals a mixture of different types of fracture morphology.…”
mentioning
confidence: 98%